Auditoría eléctrica del Centro de Operaciones El Dorado de la Empresa Eléctrica Quito S.A. - Rómulo Lozano, Ricardo Alejandro (2009)
The present work develops procedures to carry electric audits that it applies them to him in the facilities of the Center of Operations the Golden (CDOED) of the Electric Company Quito. In the electric facilities of the CDOED is carried a list of all the elements that with energy, taking in bill badge data like the power the current and the voltage that it uses each one of these elements to determine the load that is installed in this Center. Is carried the electric audit to determine the total consumption of the installed load, to identify the sector with more installed load Based on this study to know the conditions of operation of the electric system. Is determined the levels of illumination in each one of the areas of the CDOED being compared these with the values recommended in charts for each work place. The system of force has a considerable electric consumption in the heating of water intends to change this system of heating of water for a source of solar energy. This project consists of a technical analysis in order to identify actions to reduce energy consumption, and economic to determine the cost of the investment, of applying this actions. The implementation is recommended, of the alternatives proposals in this project to achieve the efficient use of the electric power that is wasting away in the facilities the CDOED.